Unpacking listening comprehension: the role of vocabulary, morphological awareness, and syntactic knowledge in reading comprehension - Gottardo, Alexandra; Mirza, Amna; Koh, Poh Wee; Ferreira, Aline; Javier, Christine (Reading & writing, 2018)
As posited by the simple view of reading, listening comprehension and decoding are necessary for reading comprehension. Thus, the present study examined subcomponents of listening comprehension (i.e., vocabulary, morphology, and syntax) and their contributions to reading comprehension. The novel aspect of this study is that rather than examining listening comprehension as a global variable, the unique and shared variance of subcomponents of listening comprehension were examined in relation to English reading comprehension. Second language learners of English from Spanish-speaking backgrounds between the ages of 9 and 13 years completed tasks assessing vocabulary, morphological awareness, syntactic knowledge, word reading, and reading comprehension in English. As expected, regression analyses showed that all three subcomponents of listening comprehension contributed to reading comprehension. Additionally, commonality analyses showed that morphological awareness and syntactic knowledge shared significant amounts of variance with vocabulary. The interrelations among these variables have implications for assessment and intervention.